The Development of an E-Module for Physical Education and Health on the Topic of Physical Activity in the Context of the Merdeka Curriculum Adaptation - Rattu Vemilla Aino; Yanuar Kiram; Donie Donie; Nuridin Widya Pranoto (JETL (Journal of Education, Teaching and Learning), 2025)
This research is intended to create an E-Module for Physical Education (PE) on physical activity games in alignment with the Merdeka Curriculum, which offers a flexible, student-centered educational approach. In the context of PE, badminton not only enhances physical fitness but also helps to shape students' character and moral values. The development of this E-Module It adopts the ADDIE model, encompassing analysis, design, development, implementation, and evaluation phases. A total of 84 seventh-grade students were selected as samples, divided into a limited trial group and a field trial group. Data collection was carried out using questionnaires. The findings of the study show that the PE badminton E-Module is highly effective when the development was carried out using the Research and Development (R&D) model following the ADDIE framework approach. This E-Module is specifically designed for seventh-grade students and integrates multimedia elements such as text, images, videos, audio, and interactivity, making it easy to use both in the classroom and at home. The validity of the E-Module is high, with scores of 90% for content, 85% for language, and 90% for media. The practicality of the E-Module is also rated very well with a score of 90%, demonstrating its ease of use for both teachers and students. Its effectiveness in improving students' understanding and motivation was proven, with a score of 92%. This E-Module is highly effective and serves as a valuable learning tool in PE, offering an engaging and interactive learning experience